PEMANFAATAN TEKNOLOGI APLIKASI UNTUK MENUNJANG KINERJA PERANGKAT DESA LAGURUDA KECAMATAN SANROBONE KABUPATEN TAKALAR - Kurniawan Kurniawan; Guntur Suryo Putro; Hikmah Hikmah (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
Application by the village apparatus of Laguruda Village, Sanrobone District, Takalar Regency. This research is a descriptive study with a qualitative approach, because the data generated in this study are in the form of written or spoken words. The key informant of the research was the Head of Laguruda Village, Sanrobone District, Takalar Regency. Supporting informants consist of the Village Secretary, the Head of Government and the Head of Services, the Head of Welfare, the Head of Finance, the Head of Planning and the Head of Administration and General Affairs. Collecting data using observation, interview, and documentation techniques. Data analysis using data collection, data reduction, data presentation, drawing conclusions. The validity of the data was determined using the source triangulation technique.The results of the study show the following: (1)data processing tasks which include transmitting data, storing data and displaying data have not been running well because village officials have not optimized the use of existing technology (2)the use of technology in facilitating administrative work is not optimal due to limited expertise the use of computer applications (3)the use of Application Technology in developing the capability of Village apparatus is still not being realized (4)the use of Application Technology in supporting and improving the quality of work is still low (5)the use of Application Technology in improving the quality and quantity of public services has not increased due to limitations in operating computers and knowledge of computer applications (6)the use of Technology in encouraging village progress is still low because it has not utilized Application Technology properly and correctly. This can be seen from the large number of village administration jobs that are maximal and often experience delays. Keywords: utilization, application technology, village apparatus